Bahan Ajar Menulis Artikel Opini dengan Metode Pembelajaran Curah Gagasan - Sahrul Romadhon; Dawud Dawud; Imam Agus Basuki (Pascasarjana Universitas Negeri Malang, 2018)
This research and development aims to produce a product of teaching materials to write opinion articles to improve the ability to write opinion articles for students of class XII. In particular, the purpose of this research and development is to develop teaching materials to write opinion articles with Brainstorming method in the class XII students packed in a printed book. To achieve these objectives used the modification of Borg and Gall learning design development. Teaching materials to write opinion articles for students of class XII is a product developed by containing four competencies to write opinion articles. The four competencies are (1) competence in writing facts and opinions, (2) writing reasoning competence, (3) competence of text structure of opinion, and (4) writing text competence and opinion article. Penelitian dan pengembangan ini bertujuan menghasilkan produk bahan ajar menulis artikel opini untuk meningkatkan kemampuan menulis artikel opini bagi siswa kelas XII. Secara khusus, tujuan penelitian dan pengembangan ini adalah mengembangkan bahan ajar menulis  artikel  opini dengan metode Curah Gagasan pada siswa kelas XII yang dikemas dalam buku cetak. Untuk mencapai tujuan  tersebut digunakan modifikasi pengembangan desain pembelajaran Borg dan Gall. Bahan ajar menulis artikel opini untuk siswa kelas XII merupakan produk yang dikembangkan dengan memuat empat kompetensi menulis artikel opini. Keempat kompetensi tersebut adalah (1) kompetensi penulisan fakta dan opini, (2) kompetensi penulisan penalaran, (3) kompetensi penyusunan struktur teks opini, dan (4) kompetensi penulisan teks serta artikel opini.